c-Myb regulates tumorigenic potential of embryonal rhabdomyosarcoma cells - Kaspar, Petr; Prochazka, Jan; Efenberkova, Michaela; Juhasz, Attila; Novosadova, Vendula; Sedlacek, Radislav (Scientific reports, 2019)
Rhabdomyosarcomas (RMS) are a heterogeneous group of mesodermal tumors, the most common sub-types are embryonal (eRMS) and alveolar (aRMS) rhabdomyosarcoma. Immunohistochemical analysis revealed c-Myb expression in both eRMS and aRMS. c-Myb has been reported to be often associated with malignant human cancers. We therefore investigated the c-Myb role in RMS using cellular models of RMS. Specific suppression of c-Myb by a lentiviral vector expressing doxycycline (Dox)-inducible c-Myb shRNA inhibited proliferation, colony formation, and migration of the eRMS cell line (RD), but not of the aRMS cell line (RH30). Upon c-Myb knockdown in eRMS cells, cells accumulated in G0/G1 phase, the invasive behaviour of cells was repressed, and elevated levels of myosin heavy chain, marker of muscle differentiation, was detected. Next, we used an RD-based xenograft model to investigate the role of c-Myb in eRMS tumorigenesis in vivo. We found that Dox administration did not result in efficient suppression of c-Myb in growing tumors. However, when c-Myb-deficient RD cells were implanted into SCID mice, we observed inefficient tumor grafting and attenuation of tumor growth during the initial stages of tumor expansion. The presented study suggests that c-Myb could be a therapeutic target in embryonal rhabdomyosarcoma assuming that its expression is ablated.
Keywords: Gene Expression Regulation, Neoplastic; Resting Phase, Cell Cycle; Proto-Oncogene Proteins c-myb; Cell Line, Tumor; G1 fáze; embryonální rhabdomyosarkom; regulace genové exprese u nádorů; Rhabdomyosarcoma, Embryonal; Carcinogenesis; Animals; protoonkogenní proteiny c-myb; Gene Knockdown Techniques; zvířata; karcinogeneze; myši; G1 Phase; genový knockdown; nádorové buněčné linie; Mice; G0 fáze